Amorphous/polycrystalline NiMn selenide for high-performance supercapacitors - Tang, Lun-Qiang; Zhang, Kai; Zeng, Hong-Yan; Yan, Wei; Yue, Hong-Li; Wang, Ming-Xin (The Journal of chemical physics, 2024)
Transition-metal selenides have been extensively studied as promising electrode materials for supercapacitors. Engineering amorphous/crystalline heterostructures is an effective strategy to improve rich active sites for accelerating redox reaction kinetics but still lacks exploration. In this study, an amorphous/crystalline heterostructure was designed and constructed by selenizing the self-sacrificial template NiMnS to generate amorphous Mn/polycrystalline Ni0.85Se–NiSe2 heterophase via the phase transformation from metal sulfide into metal selenide. The synergy of the complementary multi-components and amorphous/polycrystalline heterophase could enrich electron/ion-transport channels and expose abundant active sites, which accelerated electron/ion transfer and Faradaic reaction kinetics during charging/discharging. As expected, the optimal NiMnSe exhibited a high specific charge (1389.1 C g−1 at 1 A g−1), a good rate capability, and an excellent lifespan (88.9% retention). Moreover, the fabricated NiMnSe//activated carbon device achieved a long cycle life and energy density of 48.0 W h kg−1 at 800 W kg−1, shedding light on the potential for use in practical applications, such as electrochemical energy-storage devices.